The relationship of quality work life balance and the employee’s performance: a study at KPKT Putrajaya / Nurhidayah Abu Zarin and Soraya Maulat Ismail - Abu Zarin, Nurhidayah; Maulat Ismail, Soraya (Faculty of Business and Management, 2014)
This study intends to study the Relationship of Quality Work Life Balance and the Employee’s Performance. Three objectives have been set in order to achieve the purpose of the study. First objective is to study the levels of employee’s performance in KPKT. The second objective is to identify the relationship between works stress, personal life, and longer working hour. The third objective is to determine the most factors that influence the employee’s performance, So in order to achieve these objectives, a quantitative method is being use and data were collected by distributing 205 questionnaires to employee in KPKT. The data were analyzed using Descriptive Analysis, Pearson Correlation Analysis and Regression Analysis. The result shows that the levels of employee’s performance in KPKT are high. The result for the relationship between works stress, personal life and longer working hour showed that there is a weak, moderate and high relationship for each factor. The result also shows that longer working is the most factors that influence toward the employee’s performance of KPKT. In conclusion, this study has help in viewing the quality of work life balance in Malaysia and also to identify the factor that can contribute to employee’s performance. It is important to explore and to identify the factor in order to fight corruption.